The proactivity and resolutivity of the public ministry as a support for social legitimation and protection of human rights (Revista Direito em Debate, 2022)
In this critical essay, we emphasize that, with the promulgation of the CF/1988, the Public Ministry in Brazil, until then in the main exercise of prosecution in the criminal area with a timid incursion into the civil sphere, sees itself erected to the category of social promotion agent, in a Democratic Rule of Law whose fundamental objectives were the construction of a free, fair and solidary society, needing to eradicate poverty, marginalization and the reduction of social and regional inequalities, among other challenging issues. For decades it postulated, through the filing of actions before the Judiciary, individual and collective rights concerning the basic and fundamental needs of life in society, however, the legal protection pursued by this means, especially that of a collective nature, not infrequently occurred unsatisfactory, given the inadequate structures of the judging body. Alongside this, access to justice for the resolution of conflicts emerged as a fundamental right of citizens. Adoption became urgent for the Public Prosecutor’s Office – as a way of meeting the new values of a society eager for the implementation of the democratic spirit, thus performing the relevant attributions of a social transformation body, continuing to be useful and legitimated by this society – the adoption from another profile (not abandoning everything from the classic/demandist profile) rooted in initiative (proactivity) and in the resolution of conflicts, controversies and social problems (resolvability), without the need to file claims, but which would pacify and restore social interaction , with respect to human rights, representing a means of expanded access to justice. In this regard, through guidance and training of members and employees of the Public Ministry, the National Council of the Public Ministry (CNMP), with a view to encouraging extrajudicial resolution, presented self-composition methods, such as negotiation, mediation, conciliation, which can be instrumentalized. by the public civil inquiry, terms of adjustment of conduct.
Keywords: Human Rights. Public Ministry. Proactivity. Resolutivity. Social Legitimation.